Practice of sanohenic reflection as a condition of efficiency of personality coping behavior - Ярош, Ніна Сергіївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
This article is about sanohenic thinking and sanohenic reflection as a way of developing of the effectiveness of coping behaviour. There is analyzed the influence of sanohenic reflection on personality. The concept of the sanohenic reflection appeared in psychology not so far. U. M. Orlov was one of the first who started studying of the sanohenic thinking. The huge contribution was made by S. N Morozuk with her researches and developments. The sanohenic thinking can provide health and well-being of a individual. The sanohenic reflection is a mechanism to achieve the sanohenic thinking. Date are given about the results which person can achieve in the process of mastering the practice of sanohenic reflection. The purpose of the sanohenic reflection in emotional situations is to reduce the suffering of the experience of these emotions. In this article there were analized a lot of experimental researches that are proving the positive influence of the sanohenic reflection on an individual and on the effectiveness of his activity. It is described in short. The practice of sanohenic reflection is described shortly. The author talked about the main method in the practice of sanohenic reflection that is called the meditative graphics. The author emphasized the ability of the influence of the sanohenic reflection on an individual coping behaviour.